Electron-transport-driven proton pumps display nonhyperbolic kinetics: Simulation of the steady-state kinetics of cytochrome c oxidase - Brzezinski, Peter (1986)
A reaction cycle for electron-transportdriven proton pumps is proposed. It includes two distinct conformational states of the pump protein in which the primary electron acceptor has different reduction potentials. This has as an unavoidable consequence that the steady-state rate equation for the catalytic reaction driving the pump is nonhyperbolic. The model can be used to simulate experimental results for the kinetics of cytochrome oxidase (EC 1.9.3.1) in a wide range of experimental conditions (ionic strength, pH, temperature). It is thus not necessary to invoke more than one binding site for cytochrome c to account for the biphasic response of the oxidase activity to the concentration of this substrate.